The gratification paradox: Teacher innovation in urban and rural anti-corruption education - Oktavianus Lintong; Erryl Davy Lumintang; Abdul Haris Kai (Integritas: Jurnal Antikorupsi, 2025)
Corruption remains a systemic challenge in Indonesia, yet Anti-Corruption Education (PAK) often fails due to a one-size-fits-all approach. This paper addresses this gap by comparing the implementation of PAK in different urban and regency contexts to inform more effective and contextual strategies. Using an explanatory sequential mixed-methods design, this study surveyed 244 educators in Bitung City and North Bolaang Mongondow Regency. Findings reveal a "Dichotomy of Barriers": urban areas face "software" (environmental) challenges, while rural areas face "hardware" (resource) limitations, leading to different forms of "organic innovation." Most significantly, this research uncovers a "Gratification Paradox," where a high cognitive understanding of gratification coexists with widespread denial of its practice, rooted in a conflict between legal norms and the cultural tradition of gift-giving. This article demonstrates the limitations of purely cognitive-based PAK and encourages a fundamental shift towards context-sensitive policies and dilemma-based pedagogy to build deep ethical reasoning.